Analisis Komparatif Praktik Akuntansi pada Perusahaan Multinasional : Studi Kasus Laporan Keuangan Perusahaan Terdaftar di Bursa Efek Indonesia - Sri Fitriani; Putu Sri Arta Jaya Kusuma (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study aims to compare accounting practices between multinational companies, and domestic companies listed on the Indonesia Stock Exchange. The research method involves collecting data from five sample companies selected through purposive sampling method. Analyses were conducted using quantitative and qualitative approaches. The results showed significant differences in accounting practices between the two types of companies. The implications of these findings for the harmonisation of accounting standards and supervision of financial reporting practices in Indonesia are discussed in depth. The methodology of this study involved the use of purposive sampling method to select five sample companies. Analyses were conducted with a quantitative approach using t-test and qualitative approach to understand the differences in accounting practices. Descriptive statistical analysis techniques were used to describe the characteristics of the sample. Classical assumption tests were performed to ensure the reliability of the regression analysis. In addition, tests of normality, multicollinearity, heteroscedasticity, and autocorrelation were applied to validate the regression model. The results showed significant differences in accounting practices between multinational and domestic companies. Multinational companies tend to apply different recognition, measurement, and disclosure methods in their financial statements compared to domestic companies. Although specific figures were not included, these findings